Dividend Capture on the Ex-Dividend Day: Evidence from Vietnamese Stock Market - Quoc Trung Tran (Asian Academy of Management Journal of Accounting and Finance, 2017)
Vietnamese stock market is a promising laboratory to investigate the ex-day behaviour of stock price due to its special features: Firstly, the market uses periodic call auction mechanism for determining both opening and closing prices and there is no market maker. Secondly, tick size is much smaller than dividend amount. These imply that market microstructure theories are not applicable explanations. Thirdly, unlike many markets’ taxation of capital gains and dividends, there is no considerably preferential treatment of capital gains to dividends. Finally, short-selling is prohibited. Comparing the observed values of price drop to dividend ratio and their expected values under the impact of tax policy, we find that tax treatment fails to explain the anomaly in the research framework. The research findings show that abnormal returns are significantly positive and negative in the pre- and the post ex-dividend day periods respectively. Moreover, regression results and relevant analysis show supporting evidence for dividend capture theory.